2013
DOI: 10.14710/jai.v5i3.6311
|View full text |Cite
|
Sign up to set email alerts
|

Peran Plasmafaresis pada Terapi Pasien Sepsis dengan Myasthenia Gravis

Abstract: Pendahuluan : Plasmapheresis berpotensi untuk menghilangkan mediator berbahaya atau beracun dari sirkulasi . Plasmapheresis telah menunjukkan peningkatan keluaran yang bermakna pada penyakit autoimun . Kemanjuran theurapetic dan keamanan plasmapheresis dalam pengobatan pasien di sepsis berat dan syok septik telah dipelajari .Kasus : Seorang perempuan berusia 18 tahun didiagnosis dengan gagal nafas karena myasthenia gravis dan sepsis berat akibat pneumonia . Dia dirujuk dari rumah sakit lain setelah kegagalan o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…5 Plasmapheresis also benefits in myasthenic crisis with sepsis because of its ability to remove a variety of plasma pathogens, such as antibodies and other immune complexes. 6 In other studies, response rates to plasmapheresis were more than 50% compared to IVIG, including all changes from the myasthenic crisis severity scales. Studies have also found that pre-operative therapeutic plasma exchange in thymoma, such as plasmapheresis, is associated with better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…5 Plasmapheresis also benefits in myasthenic crisis with sepsis because of its ability to remove a variety of plasma pathogens, such as antibodies and other immune complexes. 6 In other studies, response rates to plasmapheresis were more than 50% compared to IVIG, including all changes from the myasthenic crisis severity scales. Studies have also found that pre-operative therapeutic plasma exchange in thymoma, such as plasmapheresis, is associated with better postoperative outcomes.…”
Section: Discussionmentioning
confidence: 87%